Verbindungen der Familie Ustinov nach Äthiopien - Smidt, Wolbert G.C. (Aethiopica, 2005)
An analysis of the Ustinov-Hall family networks in respect to Ethiopia shows a surprisingly intense involvement of family members in Ethiopian history, beginning with a German immigrant to Ethiopia during the zämänä mäsafǝnt until the late Ḫaylä Śǝllase’s government. In this article not only the factual involvement of family members is documented. Even more important, the impact of inter-cultural, inter-national origins on the creation of a genealogically based network of individuals ready to serve as cultural “bridges”, or better: practical intermediaries between two cultural spheres, is illustrated with these examples. The reconstruction of the genealogical origins of the family-network in a Šäwan (leading?) family gives occasion for the discussion and clarification of transliteration problems, traditions of name-giving and traditions of (originally oral) genealogical historiography.